The Geoarchaeology of Lake Michigan Coastal Dunes. - Lovis, William A. (Environmental research series (East Lansing, Mich.), 2012)
Complex sets of environmental factors have interacted over the past 5,000 years to affect how changes in climate, temperature, relative precipitation, and the levels of Lake Michigan influence the preservation of archaeological sites in coastal sand dunes along Lake Michigan. As a collaboration between earth scientists, archaeologists, and geoarchaeologists, this study draws on a wealth of research and multidisciplinary insights to explore the conditions necessary to safeguard ancient human settlements in these landscapes. A variety of contemporary and innovative techniques, includi.